PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. DWIGUNATAMA RINTIS PRIMA - Shella Aprianti Suci; Donny Dharmawan (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
Purpose to determine the influence of compensation and work discipline related to employees performance at PT. Dwigunatama Rintis Prima. The data used in this study was from questionnaire with 88 people as respondent. The analysis assumption was tested with multiple linear regression. The result of this study shown that: (1) Compensation positive influence and not significant to the employees performance. (2) Work discipline positive influence and significant to the employees performance. (3) Compensation and work discipline positive influence and significant simultaneously to the employees performance.